Interdimensional Correlation of Bodies in Female Ettawa Breed Goats - Muhammad Fadil; S. Suparman; J. Junaedi (Chalaza Journal of Animal Husbandry, 2018)
This study aimed to determine the correlation between body dimensions in female Ettawa crossbreed goats, which had been carried out in Rano Jaya Village, Toari District, Kolaka Regency. The parameters calculated in this study were 21 parameters from 7 body dimensions in goats and 35 study samples. Then the parameters of this study were calculated using the Correlation Coefficient formula to find the level of correlation between body dimensions in female Ettawa crossbreed goats. Based on the results of the study obtained several quantitative properties of female Ettawa crossbreed goat morphology which were observed among them were body surface size. The average linear dimension of the body surface and the standard deviation include: shoulder height (64.12 ± 3.09), chest (29.30 ± 1.72), chest circumference (80.94 ± 5.64), chest width (17.15 ± 1.64), hip height (69.21 ± 2.15), hip width (21.46 ± 3.10) and body length (65.79 ± 4.50) grouped according to physiological status. Calculating of the dimensions of the female Ettawa crossbreed goat body size did not get a perfect correlation, but there were 3 variables that had a very strong (positive) correlation, namely Chest Circumference - Hip Width (0.82), Chest Circumference - Body Length (0.83) and Hip Width - Body Length (0.83). It can be concluded that the dimensions of Ettawa crossbreed female goat's body of 21 variables observed were only three variables which had a correlation value close to 1 indicating a very strong or positively correlated relationship, and it could be said that increasing body size (x) increases body size (y).